Therapeutic potential of Medical Nutrition Therapy (MNT) in Non-Alcoholic Fatty Liver Disease (NAFLD) - Abdul-Malik Bawah; Kasim Abdulai; Priscilla Cecilia Akpene Amenya (Human Nutrition & Metabolism)
Background: Non-alcoholic fatty liver disease (NAFLD) is a common liver disorder strongly associated with metabolic syndrome, obesity, and insulin resistance, and is a significant contributor to liver-related morbidity and mortality worldwide. Medical Nutrition Therapy (MNT), focusing on dietary changes that reduce hepatic fat, improve insulin sensitivity, and regulate metabolic markers, is increasingly recognized as a key therapeutic approach for NAFLD management. Objective: This study assessed the therapeutic potential of MNT in NAFLD patients, focusing on its effects on liver function, metabolic health, and inflammation. Additionally, it examined how educational level and occupation, as components of socioeconomic status, influence MNT effectiveness. Methodology: A cohort of 200 NAFLD patients was recruited from Tamale Teaching Hospital, Central Hospital, Tamale West Hospital, and Dagbang Medical Centre and randomly assigned to either an MNT intervention group or a control group receiving standard care, which included general dietary recommendations without structured MNT, routine medical follow-up, and lifestyle advice from healthcare providers. Over a 12-month period, patients in the intervention group received personalized MNT, emphasizing a balanced diet, low glycemic index foods, and limited saturated fat intake. Key clinical data, including liver function tests (ALT, AST, GGT), metabolic markers (BMI, weight, fasting glucose, lipid profile), and inflammatory markers (C-reactive protein [CRP], tumor necrosis factor-alpha [TNF-α]), were collected at baseline and after 12 months. Regression analysis with interaction terms assessed the impact of educational level and occupational type on MNT outcomes. Results: The MNT intervention group showed significant improvements in liver function tests (ALT and AST decreased by 25 % on average, p < 0.01) and metabolic markers (BMI reduced by 3 %, p < 0.01). Inflammatory markers also improved, with CRP and TNF-α levels decreasing significantly compared to the control group (p < 0.01 and p < 0.05, respectively). In contrast, the control group exhibited only minimal changes in these parameters, with non-significant reductions in ALT, AST, BMI, and inflammatory markers (p > 0.05), reinforcing the added benefit of structured MNT over general dietary advice. Higher educational levels and occupations with greater health literacy were independently associated with enhanced outcomes, suggesting that these socio-demographic factors moderated MNT's effectiveness. Therefore, integrating MNT into NAFLD treatment guidelines, enhancing health provider training, expanding access, and prioritizing public education will improve outcomes and prevent disease progression. Conclusion: MNT effectively manages and provides superior benefits in NAFLD by improving liver function, metabolic health, and inflammation compared to general dietary advice and standard medical care. Socio-demographic factors like education and occupation significantly influenced MNT outcomes in NAFLD management for optimal therapeutic success.